Improving the Optical Performance and Life Time of Deep Uv Leds by Thermoelectric Control - Gramsch-Labra, E; Raff-Biggemann, U; Soto-Ormeno, C; Fredes-Donoso, P (OSA - The Optical Society, 2017)
A thermoelectric control system using thermoelectric cooler devices, allows to improve considerably the optical performance of deep UV LEDs operating at desired temperatures. Such a system was implemented monitoring and controlling temperature and optical intensities.